MINIMNYA PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DAN DAMPAKNYA TERHADAP KEAKTIFAN BELAJAR ANAK USIA DINI - Feris Kurniyati; Nisanur Naswa Sabina; Zahara Salsabila Ardea; Nurrohmi Octriana Putri; Aisya Az-Zahra; Zeskia Nafisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The use of interactive learning media in early childhood education (ECE) settings remains limited in many regions, including areas far from urban centers. This condition directly impacts children's learning activeness, which should receive optimal stimulation during the golden age period. This article aims to examine various literatures regarding the types of interactive learning media, the factors behind their minimal use, and the impacts on early childhood learning activeness. The method used is a systematic literature review analyzing 18 national journal articles published between 2020 and 2025. The results show that interactive learning media, including educational videos, educational games, augmented reality (AR) and virtual reality (VR)-based multimedia, artificial intelligence (AI)-based applications, and locally-cultured media, significantly improve the activeness, motivation, and learning outcomes of early childhood. Conversely, the minimal use of interactive media results in low child engagement in the learning process, decreased learning motivation, and inhibited language and cognitive development. Contributing factors include limited teacher pedagogical competence in utilizing technology, insufficient supporting facilities and infrastructure, and low awareness of the importance of technology-based media in early childhood education. This article recommends improving teacher competence, providing adequate infrastructure, and developing learning media integrated with local cultural values as concrete efforts to improve early childhood learning activeness.